Pattern of injuries and management of adolescent trauma in a combined adult and paediatric major trauma centre in United Kingdom. (January 2021) - Anwar, Fahim; Mee, Harry; Allanson, Judith; Mendis, Elly; Hamilton, Colin
Background: Major trauma is a leading cause of death and disability in 16–18-year olds in the UK. Since the launch of major trauma centres (MTCs) in 2012 in UK, survival rates have improved on the whole. The aim of this study was to look at the pathways of 16–18-year olds through one MTC and patterns of rehabilitation provision. Material and methods: A retrospective case notes review of all trauma patients aged between 16 and 18 years admitted to one MTC between October 2012 and May 2018. Results: One hundred forty-seven young people were identified. 67.3% were male with a mean age of 17.1 years. Motor vehicle accidents were the most common cause of injury (59.2%). Thirty-nine percent had a Glasgow Coma Scale at scene >13. Sixty-three percent were admitted to an adult intensive care unit (ICU), 5.4% to paediatric ICU and 31.3% directly to a ward. Admissions to rehabilitation ward came through adult services with no commissioned equivalent in those admitted to paediatrics. Mean length of stay was 18.1 days. 75.5% of patients were discharged home from the MTC. Discussion: The majority of young people were admitted on to adult wards and were able to access commissioned services. However, such services do not provide for the specialist needs of young people, with no access to schooling or parent's accommodation. Those who were admitted to children's services missed out on commissioned rehabilitation pathways. Conclusion: Young people of transition age often fall between services. For the first time, we illustrate injury patterns and the fragmented services seen in this vulnerable patient group.